The Effect of Enterprise Risk Management on Indonesian Publicly Listed Companies' Performance - Oktaresa, Betrika (2017)
The study investigates the impact of Enterprise Risk Management on the firm’s performance. Based on a sample of 362 publicly listed Indonesia Stock Exchange Firms, the findings from the study confirm the claim that the adoption of ERM increases the shareholders' value through the firm’s performance. The presence of risk management committee, the establishment of risk management unit, and the engagement of internal auditor in risk management process generate the better firm’s performance, particularly from the market evaluation. Further test corroborates that the market evaluation is higher on the high ERM-committed firm than the firm with rudimentary ERM or without ERM system. The study contributes to the risk management discipline. Firstly, the study provides additional empirical evidence of the impact of enterprise risk management on the firm’s performance, especially in emerging countries. Secondly, the findings can be a signal for investors in Indonesia to use the company's ERM determinants information when they are assessing the firm’s performance.